Managing Innovation to Maximize Value Along the Discovery-Translation-Application Continuum - Waldman, SA (Clin Pharmacol Ther, 2016)
Success in pharmaceutical development led to a record 51 drug approved in the past year, surpassing every previous year since 1950. Technology innovation enabled identification and exploitation of increasingly precise disease targets ensuring a next generation diagnostic and therapeutic products for patient management. The expanding biopharmaceutical portfolio stands however in contradistinction to the unsustainable costs that reflect remarkable challenges of clinical development programs. This annual Therapeutic Innovations issue juxtaposes advances in translating molecular breakthroughs into transformative therapies with essential considerations for lowering attrition and improving the cost-effectiveness of the drug development paradigm. Realizing the discovery-translation-application continuum mandates a congruent approval, adoption and access triad.